Miracles, mysteries, and prayer - Berg, Philip S. (New York : Research Centre of Kabbalah, 1993)
Why do our prayers seem to go unanswered? Do miracles really exist? Can we ever know all the mysteries of our universe? In Miracles, Mysteries and Prayer, Rav Berg takes us on a compelling journey where we discover many insightful secrets revealing a mysterious connection between the universe out there and the universe within ourselves. The life-enriching concepts of Kabbalah provide a clear light onto the profound answers and solutions that we personally seek. We begin to realize that prayer can solve many of our own mysteries and create a miracle or two in our own lives as well. The ancient Kabbalists provided us with a technology for activating the power of prayer. For the first time in 2000 years, this ancient technology is being made available to the layperson.
Chapter 1. Planets -- Chapter 2. The frontiers of space -- Chapter 3. The invisible cosmos -- Chapter 4. Waves and particles -- Chapter 5. The expanding inner universe -- Chapter 6. The language of kabbalah -- Chapter 7. Prayer.
Includes bibliographical references.
Keywords: CABALA